1978
DOI: 10.1149/1.2131651
|View full text |Cite
|
Sign up to set email alerts
|

The Calcium Anode in Molten Nitrate Electrolytes

Abstract: The electrochemical behavior of the calcium anode in molten nitrates was determined using constant current methods. Investigations were made in both LiNO3 and KNO3 at 350~ and in KNO3-LiNO3 (60-40 mole percent) over a temperature range of 250~176 Differential scanning calorimetry studies were also made on calcium in many nitrate mixtures. No exothermic reactions were detected for calcium in any pure alkali metal nitrate melt; however, chemical reactions were apparent for many calcium-molten nitrate systems whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…Open-circuit cell potentials close to these calculated values have been observed at 350~ in the presence of chloride ions that attack the passivating film on the anode (8,9). Previous studies showed that Ca/LiNQ-LiC1-KC1 [50-25-25 mole percent (m/o)] thermal battery cells gave promising results when discharged at 10 mA/cm 2 over a temperature range of 250~176 (9).…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Open-circuit cell potentials close to these calculated values have been observed at 350~ in the presence of chloride ions that attack the passivating film on the anode (8,9). Previous studies showed that Ca/LiNQ-LiC1-KC1 [50-25-25 mole percent (m/o)] thermal battery cells gave promising results when discharged at 10 mA/cm 2 over a temperature range of 250~176 (9).…”
supporting
confidence: 73%
“…At current densities above 20-30 mA/cm~, however, the cell performance deteriorates due to polarization at the anode. The rate of the calcium anode reaction in molten nitrates is determined largely by the passivating film that hinders the passage of calcium ions across the oxide layer (8). Comparisons of measured and calculated cell resistances suggest that the anodic oxide film makes a sizeable contribution to the total cell resistance (9).…”
mentioning
confidence: 99%
“…Since the entropy variation for the oxide formation is negative, the free energy becomes less negative as temperature increases. Therefore, it is not surprising that the first reports on Ca metal anodes in the early 1960s (section ) were on cells operated at high temperatures (>450 °C). , The electrolyte chemistry was very similar to Ca metal production; molten salts, typically eutectic mixtures of CaCl 2 and CaF 2 , were employed and involved electrowinning and electrorefining processes performed at >850 °C . Later on, the concept of liquid metal electrodes also used higher temperatures, typically operating at >500 °C …”
Section: Anodes Electrolytes and Cathodesmentioning
confidence: 99%
“…Some attempts to modify the surface of the calcium metal anodes with acetic acid to yield CaCO 3 were reported, despite the chemistry being shown to be extremely complex involving also corrosion with formation of both Ca 2 CrO 4 Cl and KCaCl 3 . Efforts to replace the chlorides by nitrates, with lower melting points, as electrolytes were also reported . A maximum exchange of one electron per mole of calcium was observed with the formation of a passivation film most likely consisting of CaO, hindering any fast kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Portions of this work were presented as Paper 586 at the Denver, Colorado, Meeting of the Society, Oct. [11][12][13][14][15][16] 1981, and as Paper 341 at the Detroit, Michigan, Meeting of the Society, Oct. 17-21 1982. Portions of this work were presented as Paper 586 at the Denver, Colorado, Meeting of the Society, Oct. [11][12][13][14][15][16] 1981, and as Paper 341 at the Detroit, Michigan, Meeting of the Society, Oct. 17-21 1982.…”
Section: Acknowledgmentmentioning
confidence: 99%